Spatial analysis of dengue cases in a municipality in the semi-arid pernambucano (Research, Society and Development, 2021)
Brazilian semiarid is compound of more than 1,260 municipalities, comprising states of northeastern and northern Minas Gerais. Due to periods of prolonged drought, residents store water indiscriminately, favoring the proliferation of Aedes aegypti, transmitter of arboviruses. Therefore, this paper aimed to analyze the distribution of confirmed cases, as well as the number of eggs collected by ovitraps, correlating them with meteorological variables in a municipality of semiarid region. Secondary data were collected regarding the number of cases, number of eggs per ovitrap (infestation), meteorological variables for the period 2010-2013. Then, a spatial database, subsequent spatial distribution analysis using the method Inverse Distance (IDW),  statistical analysis of correlation between meteorological variables, number of confirmed cases and infestation was done. It was observed that correlation between temperature and humidity, with confirmed cases, was considered weak. While precipitation in 2012 showed a strong correlation. However, these same variables were considered weak in 2013. Regarding the spatial distribution of confirmed cases, there was a concentration in the most densely populated neighborhoods. Thus, it was concluded that geotechnology enables the identification of risk areas, helping to realize more efficient strategies.